Cureh Main Market Relocation Strategy, Bireuen Regency - Siregar, Nabila Utari (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
This study aims to determine the relocation strategy of the Cureh main market in Bireuen Regency. The method used is descriptive research method with qualitative data analysis, which is a type of research through problem solving procedures that are investigated by describing the circumstances surrounding the research object based on facts and the data collection technique used is interview technique. Based on the results of this study, it is known that the relocation strategy of the Cureh Main Market, Bireuen Regency has been running effectively, such as the responsibilities of the Office of Investment, Trade, Cooperatives and SMEs which have been implemented properly. Supervision carried out by the Office of Investment, Trade, Cooperatives and SMEs of Bireuen Regency is carried out by monitoring the relocated traders in the Cureh Main Market and confirming the traders who are still selling in the old market. Then the facilities provided by the Office of Investment, Trade, Cooperatives and SMEs have a level of equality and can meet the needs of traders, but there is no coordination between the service and local companies. It is hoped that the Office of Investment, Trade, Cooperatives and SMEs will be more responsible for the traders who were relocated to the Cureh Main Market so that there are no more complaints from traders. The Office of Investment, Trade, Cooperatives and SMEs will maximize supervision of traders who have been relocated to the Cureh Main Market, especially for traders who are still in the old market. has been provided, the Bireuen Regency Government to be able to form a regional company that can coordinate with the existing market in Bireuen Regency so that it can run effectively. Keywords: Strategy, Market Relocation